Successful Control of a Colistin and Carbapenem Resistant Klebsiella pneumoniae Outbreak in an Intensive Care Unit - Ahsen Öncül; Aziz Ahmad Hamidi; Dilek Yıldız Sevgi; İlkay Ordu Balık; Zuhal Kalaycı Çekin; Mehmet Emin Bulut; Barış Otlu; Elif Aktaş (Cam & Sakura Medical Journal, 2025)
Objective: Multi-drug-resistant bacteria burden is rising in both developing and high-income countries. We describe here a cluster of colistin and carbapenem-resistant K. pneumoniae, (CCRKP) in an educational and training hospital in Turkey, mainly associated with intensive care unit (ICU) stays. Material and Methods: After CCRKP growth was detected in the microbiological samples of 21 patients who had a history of ICU hospitalization and were admitted to the hospital currently, the situation was classified as an epidemic. Rectal and environmental surveillance cultures were obtained. Carbapenemase production was tested by carbapenem inactivation method, and carbapenemase genes, including blaOXA-48, blaNDM-1, blaKPC, blaVIM, blaIMP and blaGES, were investigated by multiplex polymerase chain reaction (PCR). mcr1/2 genes associated with plasmid-mediated colistin resistance were investigated by PCR. CCRKP isolated from rectal and environmental screenings were evaluated further for epidemiologic relationships with clinical isolates. Pulsed-field gel electrophoresis was done using Xba-I enzyme for digestion. Results: CCRKP rectal colonization prevalence was 57% (8/14) on the screening day. Five of these eight patients were colonized only, and none of these asymptomatic carriers developed infection. CCRKP was detected on an infusion pump, which was used for some of the previous patients and was suspected to be a cross contamination source. The outbreak isolate was found to be of genotype A; OXA-48 positive, NDM negative by PCR. mCR gene 1/2 was negative. One of the infected patients and one of the colonized patients isolates were different, and the remaining 22 isolates were indistinguishable. After strict infection control interventions, eight cases were detected in a five month period. Rectal swabbing was stopped after no new cases had been observed for two months. CCRKP hasn’t been detected in clinical specimens for one year since then. Conclusion: Environmental screening and isolation of colonized patients have a crucial role in controlling outbreaks of multidrug-resistant Gram-negative bacteria.